Assessing the Associations of the Parental Beliefs and Practices about Child Feeding and its Impact on Child Weight - Azza Ismail Ismail El Sayed, Safaa, T. Almanzalwi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Prevalence of overweight, obesity among children age in Egypt and severe obesity among of all age groups varies very high, children’s obesity is an alarming issue. Continually rising prevalence of obesity and overweight in children is a major public health concern. This is due to its various and serious health hazards on one side and its preventable nature on the other side. The problem primarily relies on the ability of parents to recognize their child’s overweight/obesity, and to be aware that obesity is a risk factor for long-term health issues. Several studies showed that many parents are not concerned about their children’s body weight, because they either think too little of their child’s body weight or believe that obesity is inherited, thus modifiable. Parent’s perception of child feeding is one of the influencing causes that contribute to child weight status. Although the prevalence of childhood obesity has increased significantly in Egypt, parents are unable to appreciate obesity in their child. Parental beliefs and practices in children’s nutrition may determine deviations in the acquisition of the child’s food preferences and in their self-regulation, who can influence their nutritional status. Childhood obesity and metabolic complications related thereto emerge as a challenge to global health in the 21st century, given its dramatic increase in the last decade in most countries Aim of the study: to assess of parental beliefs and practices about child feeding and its impact on child weight. Setting: The research was conducted on sample of parents (mother, father, children), living in some regions at Menoufia Governorate, Egypt. Method: Cross-sectional and descriptive study developed in a sample of (388) parents’ study children aged 6-10 years. The children were recruited from the primary schools located in Al- Menoufia region, Egypt. Child feeding, beliefs about childhood obesity, and practices about child feeding were collected. The body mass index of the children was assessed in the school, and their parents responded to a self-administered questionnaire which contained questions on parental perception of the children’s weight/obesity status. Data were entered and analyzed using SPSS. Results: There were 388 participants, were the data ranged from (23to76) by mean+ SD (42.172±7.970). The majority of them were male (79.1%), while female (20.9%). The most of the participants was married (59.3%). Child’s age were the data ranged from(6to18)by mean+ SD (9.734±2.244 (. Child should always eat all of the food on her plate almost of the parental answer is slightly agree were (33.8%) followed by agree (21.9%) while % of agreement (68.35%), regarding I have to be especially careful to make sure my child eats enough the majority of parental answer agree were (67.5%) followed by slightly agree were (17.5%)while % of agreement (89.54%). Conclusion: This study highlights the importance of being aware of child’s weight status when feeding practices were provided to them. Since influence’s which promote obesity in children include numerous factors, this issue must be handled as one of the greatest social and public health challenges at the present time. Nutrition education for parents should take account for parents’ perceptions and concerns as well as the modification of feeding practices to improve children’s eating behaviors. Pressures to eat were related to overweight children.